2010
DOI: 10.1262/jrd.10-006t
|View full text |Cite
|
Sign up to set email alerts
|

Estrus Synchronization with Pseudopregnant Gilts Induced by a Single Treatment of Estradiol Dipropionate

Abstract: Abstract. The aims of this study were to determine whether a single treatment of estradiol dipropionate (EDP) could induce pseudopregnancy in gilts and to determine the effectiveness of PGF2α treatment on estrus synchronization in EDP-induced pseudopregnant gilts. In experiment 1, gilts were treated with 20 mg of EDP (n=11) or vehicle (n=5) on Day 12 (Day 0=onset of estrus). Establishment of pseudopregnancy was defined as a lack of estrus and maintenance of the plasma progesterone concentration above 1 ng/ml b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 34 publications
(70 reference statements)
8
40
0
Order By: Relevance
“…The decrease in progesterone levels to under 1 ng/ ml in pseudopregnant females induced by multiple injections of EB [5] and a single injection of EDP [17,18] occurred 21 − 57 hr and 24 − 48 hr after dinoprost treatment, respectively. In the present study, estrus was mainly observed 5 and 6 days after cloprostenol treatment similarly to dinoprost treatment in pseudopregnant females treated with EB [9,13] or EDP [17,18]. The present results and previous reports indicate that cloprostenol and dinoprost have equivalent effects on luteolysis and subsequent estrus exhibition in pseudopregnant females.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The decrease in progesterone levels to under 1 ng/ ml in pseudopregnant females induced by multiple injections of EB [5] and a single injection of EDP [17,18] occurred 21 − 57 hr and 24 − 48 hr after dinoprost treatment, respectively. In the present study, estrus was mainly observed 5 and 6 days after cloprostenol treatment similarly to dinoprost treatment in pseudopregnant females treated with EB [9,13] or EDP [17,18]. The present results and previous reports indicate that cloprostenol and dinoprost have equivalent effects on luteolysis and subsequent estrus exhibition in pseudopregnant females.…”
Section: Discussionmentioning
confidence: 95%
“…Animals were checked for estrus twice daily from 17 days after ovulation, and pseudopregnancy was defined as absence of estrus maintained until at least 20 days after EDP treatment, as described previously [17]. Pseudopregnant sows were treated with PGF 2α -A as 0.175 mg cloprostenol (Planate, Intervet, Osaka, Japan) intramuscularly twice over a 24-hr interval between 24 and 28 days after EDP treatment.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations